Abundance interaction in Candida albicans and Candida glabrata mixed biofilms under diverse conditions. (26th May 2020) - Li, Qianqian; Liu, Juanjuan; Chen, Mengli; Ma, Kelong; Wang, Tianming; Wu, Daqiang; Yan, Guiming; Wang, Changzhong; Shao, Jing
Abstract: Candida albicans and Candida glabrata are frequently coisolated from the oral cavity in immunosuppressive or immunocompromised individuals. Their relationship is usually defined as competition as C. glabrata can inhibit growth of C. albicans in cohabitation. In this study, eight C. albicans isolates as well as two C. glabrata strains were used to investigate the effects of culture medium (Roswell Park Memorial Institute [RPMI]-1640, YPD, YND), incubation time (24 h, 48 h, 72 h, 96 h), initial inoculum ( C. glabrata: C. albicans = 2:1, 1:1, 1:2), and medium state (static and dynamic states) on viable cell enumeration and relative abundance in both Candida SB and MB. The results showed that in most cases, C. glabrata and C. albicans SB and MB flourished in RPMI-1640 at 24 h under dynamic state compared with other conditions. Except YPD medium, there were high proportions of preponderance of C. albicans over C. glabrata in MB compared with SB. High initial inoculum promoted corresponding Candida number in both SB and MB and its abundance in MB relative to SB. This study revealed an impact of several environmental conditions on the formation of C. albicans and C. glabrata SB and MB and their abundance in MB in comparison with SB, deepening our understanding of both Candida interaction and their resistance mechanism in MB. Lay Summary: This study described the effects of diverse experimental conditions on the numbers of Candida albicans and Candida glabrata single biofilms and mixed biofilms and their abundance.